2020
DOI: 10.1007/s10765-020-02681-0
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Correlation of the Thermal Conductivity of cis-1,1,1,4,4,4-hexafluoro-2-butene

Abstract: New experimental data for the thermal conductivity of cis-1,1,1,4,4,4-hexafluoro-2-butene (R-1336mzz(Z)) are reported for vapor, liquid and supercritical states. These data were obtained with transient hot-wire apparatus over the temperature range from 192 K to 498 K and at pressures from 0.05 MPa to 69 MPa. These data were used to develop a wide-range correlation for the thermal conductivity of the vapor, liquid, and supercritical fluid. The experimental data reported here have an uncertainty of 1 % for the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…(a) Deviations from experimental data ,, as a function of reduced pressure for three refrigerants at T r = 0.96–0.97. (b) RES and ECS deviations for R-134a as a function of reduced pressure at T r = 0.97.…”
Section: Resultsmentioning
confidence: 99%
“…(a) Deviations from experimental data ,, as a function of reduced pressure for three refrigerants at T r = 0.96–0.97. (b) RES and ECS deviations for R-134a as a function of reduced pressure at T r = 0.97.…”
Section: Resultsmentioning
confidence: 99%
“…Although the calculation of thermal conductivity through eqs – is so complicated that it is difficult to specify a cause of the large systematic deviations, the correlation models involving the density such as eqs – or possibly yield a different estimation for the contribution to the thermal conductivity of R1336mzz(E). On the one hand, Perkins et al reported that their measurements of thermal conductivities for R1336mzz(Z) were systematically 10 × 10 –2 higher than the measurements by Alam et al, which were obtained by using the same apparatus as Mondal et al Therefore, the third-party measurements for thermal conductivity of R1336mzz(E) should be required to rightly explain the reproducibility or validity for the correlation models in eqs –.…”
Section: Thermophysical Properties Evaluationmentioning
confidence: 99%
“…The experimental data of the saturated liquid thermal conductivity for HFO-1234ze­(E) were obtained by Gerebenkov et al and Perkins and Huber, respectively. The vapor, superheat liquid, liquid, and supercritical states thermal conductivities of HFO-1336mzz­(Z) were measured by Alam et al and Perkins and Huber . However, the saturated liquid thermal conductivity data of HFO-1336mzz­(E) have not been reported so far.…”
Section: Introductionmentioning
confidence: 98%
“…The vapor, superheat liquid, liquid, and supercritical states thermal conductivities of HFO-1336mzz(Z) were measured by Alam et al 5 and Perkins and Huber. 35 However, the saturated liquid thermal conductivity data of HFO-1336mzz(E) have not been reported so far. It is well known that the saturated liquid thermal conductivity of HFO refrigerants is of great practical significance.…”
Section: Introductionmentioning
confidence: 99%